2017
DOI: 10.1155/2017/9671816
|View full text |Cite
|
Sign up to set email alerts
|

Approximate Solutions of Schrodinger Equation with Some Diatomic Molecular Interactions Using Nikiforov-Uvarov Method

Abstract: We used a tool of conventional Nikiforov-Uvarov method to determine bound state solutions of Schrodinger equation with quantum interaction potential called Hulthen-Yukawa inversely quadratic potential (HYIQP). We obtained the energy eigenvalues and the total normalized wave function. We employed Hellmann-Feynman Theorem (HFT) to compute expectation values ⟨ −2 ⟩, ⟨ −1 ⟩, ⟨ ⟩, and ⟨ 2 ⟩ for four different diatomic molecules: hydrogen molecule (H 2 ), lithium hydride molecule (LiH), hydrogen chloride molecule (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…which is good agreement with the result in Equation ( 28) (If B and C are considered zero as a special case) of Ref [31]. Generally, it is obviously seen from Equation.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…which is good agreement with the result in Equation ( 28) (If B and C are considered zero as a special case) of Ref [31]. Generally, it is obviously seen from Equation.…”
Section: Resultssupporting
confidence: 91%
“…Nonetheless, Okon et al reported analytical solutions of the Schrödinger equation for the Hulthén-Yukawa plus inversely quadratic potential. [31] In Ref. [32][33][34][35][36][37][38][39], the scalar potential, which is nonequal and equal to the vector potential, was supposed to get the bound states of the KFG equation for some typical potential from the ordinary quantum mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…The NU method is based on reducing second order linear differential equation to a generalised equation of hyper-geometric type and provides exact solutions in terms of special orthogonal functions like Jacobi and Laguerre as well as corresponding energy eigenvalues 73 78 . The standard differential equation for parametric NU method according to Tezcan and Sever 79 is given as The parametric constants are obtained as follows The condition for energy equation is given as The corresponding total wave function is then given as …”
Section: The Parametric Nikiforov–uvarov (Nu) Methodsmentioning
confidence: 99%
“…Eigen-solutions to relativistic and nonrelativistic wave equations has been of growing interest for decades because of its applications to some physical systems. The Schrodinger wave equation constitute the nonrelativistic wave equation while Klein-Gordon and Dirac constitutes the relativistic wave equations [1][2][3][4][5][6][7][8]. Most potentials are modelled and applied to solve some physical systems examples include: Morse potential, Tietz-Wei, pseudoharmonic, Deng-Fan, Kratzer -Feus, Mie-Type and many of exponential -type potentials [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%